Morphogenetic responses of cuttings and in vitro plants of Vanilla planifolia (Orchidaceae) during initial development in greenhouse and agroforestry systems - Azofeifa Bolaños, José Bernal (2018)
There is little knowledge in Costa Rica about morphogenetic responses of Vanilla planifolia. Here we compare cutting and micro-cutting for morphogenetic response in nursery and agroforestry. Each plant type was grown in both conditions and the combination with factor levels resulted in four treatments. The independent growth responses of the cuttings were significantly higher for the length, total weight and emergent shoot, total and average length and weight of the roots compared to that in micro-cuttings. For this factor, a significant increase of nodes was achieved when micro-cuttings were used. The length, total weight and emergent shoot, weight and number of roots of the explants grown in the field were significantly greater compared to that in nursery. Total and average length of the roots did not significantly differ between independent treatments of condition factor. Significant interaction between factors were obtained for all variables except for the total weight and the emergent shoot. After a period of nursery acclimatization, the agroforestry vitroplants were significantly higher for the length of the shoot, number of nodes and number of roots in relation to the cuttings grown in both conditions, as well as the vitroplants grown in nursery. Longer and heavier roots were obtained when cuttings were grown at the nursery, suggesting a more intense growth in the search for water and nutrients.